Climate Risk Stress Test: Impact of Climate Change on the Peruvian Financial System - Romero, Daniel (2024)
We develop the first climate risk Stress Test for the Peruvian financial system following a topdown approach. Focusing on the microeconomic channel, we evaluate how heavy rainfall and droughts, under a scenario of pure physical risk, will marginally affect the probability of default (PD) of borrowers by 2050. Using information from the Credit Registry, the National Oceanic and Atmospheric Administration (NOAA), and CMIP6 precipitation projections (37 modeling groups), we calibrate the marginal impacts differentiating by economic sector and geographical location. We find that, on average, by December 2050, the probability of default of the Peruvian financial system would increase by 4.9% with respect to December 2020. By geographic area, borrowers located on the northern coast (Piura, Lambayeque) and the southern highlands (Ayacucho, Cusco) would be negatively affected by heavy rainfall, while the rainforest (Madre de Dios, Ucayali) would be negatively affected by droughts. Moreover, the economic sectors affected by heavy rainfall or droughts would be agriculture, commerce, and transportation & communications.